Pendampingan Pembuatan Es Puter Alpukat Pada UMKM Es Cream “Cak Ndut” di Kelurahan Sukorejo - Fasya Arifatin; Chrystia Aji Putra; Dhikma Pristika Melenia (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Avocados contain high amounts of fat. The fatty acids in avocados 60-80% are monounsaturated fatty acids. The predominant fatty acids in avocado oil are oleic (67-72%), palmitic (13-10%), palmitoleic (3-5.1%), and linoleic (10.4-12%). And the rest is linolenic (1.5%). The high oleic acid content in avocados is good for adding to ice puter. This study aims to perform organoleptic tests on the sensory properties of es puter in the form of aroma, color, texture, and taste in each different treatment using hedonic tests so that the best es puter can be determined in terms of sensory properties. There were two experiments conducted, namely the characteristic experiment of avocado ice puter with vegetable fat sources and avocado ice puter with animal fat sources. The results showed that the addition of cow's milk to the ice puter had a more fragrant avocado aroma, while the addition of soy milk to the ice puter did not smell avocado. The addition of cow's milk to the ice puter is darker green in color, while the addition of soy milk to the ice puter is pale green. The addition of cow's milk to the ice puter has a smooth texture, while the addition of soy milk to the ice puter has a slightly coarse texture.